The interaction between cucurbit[8]uril and baicalein and the effect on baicalein properties - Zhang, Xiaodong; Xie, Jun; Xu, Zhiling; Tao, Zhu; Zhang, Qianjun (Beilstein Journal of Organic Chemistry, 2020)
The host–guest interactions between baicalein (BALE) and cucurbit[8]uril (Q[8]) and the corresponding properties of the inclusion complex were studied using 1H NMR, IR and UV–vis spectroscopy and DTA. The results showed that BALE forms an inclusion compound (1:1) with Q[8], and the properties of baicalein are changed by cucurbit[8]uril.
Keywords: baicalein; cucurbit[8]uril; host–guest interaction; inclusion complex; properties

(untitled) - Haslam, E. (J. Nat. Prod., 1996)

(untitled) - Kumar Roy, M.; Nakahara, K.; Na Thalang, V.; Trakoontivakorn, G.; Takenaka, M.; Isobe, S.; Tsushida, T. (Pharmazie, 2007)

(untitled) - Zhou, R. T.; He, M.; Yu, Z.; Liang, Y.; Nie, Y.; Tai, S.; Teng, C. B. (Oncotarget, 2017)

(untitled) - Wang, Y.-F.; Xu, Y.-L.; Tang, Z.-H.; Li, T.; Zhang, L.-L.; Chen, X.; Lu, J.-H.; Leung, C.-H.; Ma, D.-L.; Qiang, W.-A.; Wang, Y.-T.; Lu, J.-J. (Am. J. Chin. Med., 2017)

(untitled) - Palko-Labuz, A.; Sroda-Pomianek, K.; Uryga, A.; Kostrzewa-Suslow, E.; Michalak, K. (Biomed. Pharmacother., 2017)

(untitled) - Chai, Y.; Xu, J.; Yan, B. (Oncol. Rep., 2017)

(untitled) - Bie, B.; Sun, J.; Li, J.; Guo, Y.; Jiang, W.; Huang, C.; Yang, J.; Li, Z. (Cell. Physiol. Biochem., 2017)

(untitled) - Rui, X.; Yan, X.; Zhang, K. (Oncol. Lett., 2016)

(untitled) - Nguyen, L. T. T.; Song, Y. W.; Cho, S. K. (Mol. Cells, 2016)

(untitled) - Mu, J.; Liu, T.; Jiang, L.; Wu, X.; Cao, Y.; Li, M.; Dong, Q.; Liu, Y.; Xu, H. (J. Cancer (Wyoming, Aust.), 2016)

(untitled) - Ma, X.; Yan, W.; Dai, Z.; Gao, X.; Ma, Y.; Xu, Q.; Jiang, J.; Zhang, S. (Drug Des., Dev. Ther., 2016)

(untitled) - Choi, E.-O.; Park, C.; Hwang, H.-J.; Hong, S. H.; Kim, G.-Y.; Cho, E.-J.; Kim, W.-J.; Choi, Y. H. (Int. J. Oncol., 2016)

(untitled) - Cathcart, M.-C.; Useckaite, Z.; Drakeford, C.; Semik, V.; Lysaght, J.; Gately, K.; O’Byrne, K. J.; Pidgeon, G. P. (BMC Cancer, 2016)

(untitled) - Guo, Z.; Hu, X.; Xing, Z.; Xing, R.; Lv, R.; Cheng, X.; Su, J.; Zhou, Z.; Xu, Z.; Nilsson, S.; Liu, Z. (Mol. Cell. Biochem., 2015)

(untitled) - Zheng, Y.-H.; Yin, L.-H.; Grahn, T. H. M.; Ye, A.-F.; Zhao, Y.-R.; Zhang, Q.-Y. (Phytother. Res., 2014)

(untitled) - Li, H.-L.; Zhang, S.; Wang, Y.; Liang, R.-R.; Li, J.; An, P.; Wang, Z.-M.; Yang, J.; Li, Z.-F. (Mol. Med. Rep., 2013)

(untitled) - Kim, D. H.; Hossain, M. A.; Kang, Y. J.; Jang, J. Y.; Lee, Y. J.; Im, E.; Yoon, J.-H.; Kim, H. S.; Chung, H. Y.; Kim, N. D. (Int. J. Oncol., 2013)

(untitled) - Kim, S.-J.; Kim, H.-J.; Kim, H.-R.; Lee, S.-H.; Cho, S.-D.; Choi, C.-S.; Nam, J.-S.; Jung, J.-Y. (Mol. Med. Rep., 2012)

(untitled) - Chen, C.-H.; Huang, T.-S.; Wong, C.-H.; Hong, C.-L.; Tsai, Y.-H.; Liang, C.-C.; Lu, F.-J.; Chang, W.-H. (Food Chem. Toxicol., 2009)

(untitled) - Motoo, Y.; Sawabu, N. (Cancer Lett., 1994)

(untitled) - Bonham, M.; Posakony, J.; Coleman, I.; Montgomery, B.; Simon, J.; Nelson, P. S. (Clin. Cancer Res., 2005)

(untitled) - Ma, Z.; Otsuyama, K.-i.; Liu, S.; Abroun, S.; Ishikawa, H.; Tsuyama, N.; Obata, M.; Li, F.-J.; Zheng, X.; Maki, Y.; Miyamoto, K.; Kawano, M. M. (Blood, 2005)

(untitled) - Liu, H.; Dong, Y.; Gao, Y.; Du, Z.; Wang, Y.; Cheng, P.; Chen, A.; Huang, H. (Int. J. Mol. Sci., 2016)

(untitled) - Gao, Y.; Snyder, S. A.; Smith, J. N.; Chen, Y. C. (Med. Chem. Res., 2016)

(untitled) - Shieh, D. E.; Liu, L. T.; Lin, C. C. (Anticancer Res., 2000)

(untitled) - Li, J.; Ma, J.; Wang, K. S.; Mi, C.; Wang, Z.; Piao, L. X.; Xu, G. H.; Li, X.; Lee, J. J.; Jin, X. (Oncol. Rep., 2016)

(untitled) - Patwardhan, R. S.; Sharma, D.; Thoh, M.; Checker, R.; Sandur, S. K. (Biochem. Pharmacol., 2016)

(untitled) - Tsai, K.-L.; Hung, C.-H.; Chan, S.-H.; Shih, J.-Y.; Cheng, Y.-H.; Tsai, Y.-J.; Lin, H.-C.; Chu, P.-M. (Oncotarget, 2016)

(untitled) - Zhao, F.; Fu, L.; Yang, W.; Dong, Y.; Yang, J.; Sun, S.; Hou, Y. (Life Sci., 2016)

(untitled) - Sahu, B. D.; Kumar, J. M.; Sistla, R. (PLoS One, 2015)

(untitled) - Zhou, Q.-n.; Wei, X.-h.; Wang, Z.-t. (Shanghai J. Tradit. Chin. Med., 2013)

(untitled) - Zhang, X.; Shi, X.; Su, S.; Zhou, G.; Ni, X.-L. (Dyes Pigm., 2020)

(untitled) - Cong, H.; Ni, X. L.; Xiao, X.; Huang, Y.; Zhu, Q.-J.; Xue, S.-F.; Tao, Z.; Lindoy, L. F.; Wei, G. (Org. Biomol. Chem., 2016)

(untitled) - Huang, Y.; Tao, Z.; Xue, S. F.; Zhu, Q. J. (Chem. J. Chin. Univ., 2011)

(untitled) - Li, M.; Lian, X.; Xu, Z.; Xing, X.; Zhang, J.; Li, R.; Tao, Z.; Zhang, Q. (Chem. J. Chin. Univ., 2017)

(untitled) - Wang, C.-H.; Tang, Q.; Zhang, J.; Yao, Y.-Q.; Xiao, X.; Huang, Y.; Tao, Z. (New J. Chem., 2018)

(untitled) - Meng, L.-J.; Zhao, W.-X.; Chen, L.-X.; Sun, W.-Q.; Lin, R.-L.; Zhu, Q.-J.; Tao, Z.; Liu, J.-X. (ChemistrySelect, 2018)

(untitled) - Gao, Z.-Z.; Lin, R.-L.; Bai, D.; Tao, Z.; Liu, J.-X.; Xiao, X. (Sci. Rep., 2017)

(untitled) - Fan, Y.; Gao, Z.-Z.; Zhao, W.-X.; Chen, S.-Y.; Xi, Y.-Y.; Gao, R.-H.; Xiao, X.; Tao, Z. (J. Inclusion Phenom. Macrocyclic Chem., 2017)

(untitled) - Zhao, W.-X.; Wang, C.-Z.; Chen, L.-X.; Cong, H.; Xiao, X.; Zhang, Y.-Q.; Xue, S.-F.; Huang, Y.; Tao, Z.; Zhu, Q.-J. (Org. Lett., 2015)

(untitled) - Alfonsi, R.; Attivi, D.; Astier, A.; Socha, M.; Morice, S.; Gibaud, S. (Ann. Pharm. Fr., 2013)

(untitled) - Lee, B. W.; Lee, J. H.; Gal, S. W.; Moon, Y. H.; Park, K. H. (Biosci., Biotechnol., Biochem., 2006)

Chinese Pharmacopoeia, 2015, Section Two - Chinese Pharmacopoeia Commission (China Medical Science and Technology Press, 2015)

(untitled) - Yang, C.; Wang, Z.; Ou, C.; Chen, M.; Wang, L.; Yang, Z. (Chem. Commun., 2014)

(untitled) - Xu, Z.; Lian, X.; Li, M.; Zhang, X.; Wang, Y.; Tao, Z.; Zhang, Q. (Chem. Res. Chin. Univ., 2017)

(untitled) - Huang, J.; Xu, Z.; Lian, X.; Zhang, X.; Tao, Z.; Zhou, Q.; Zhang, Q.; Wei, G. (Chem. J. Chin. Univ., 2018)